The Effectiveness of Group Counseling Using Self-Counseling Techniques to Increase Students' Learning Motivation - Niswatul Baroroh; Eva Imania (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Lack of motivation to learn influences the decline in student academic achievement and exam results, as experienced by class XII students at MAN 1 Deli Serdang, North Sumatra. This research aims to determine the effectiveness of group counseling services using the Counseling Self technique in increasing students' learning motivation. This is a type of quasi-experimental research with an unequal control group research design. The sample was determined using a purposive sampling technique, with respondents totaling 68 students in class XII MAN I Deli Serdang, North Sumatra. The results show that after being given treatment, namely group counseling services using the Self Counseling technique, in the experimental group, there was a significant increase in students' learning motivation. This can be proven by research results and the increase in students' academic results. From the results of research using self-counseling techniques where the higher the social support to increase students' learning motivation, it is hoped that BK teachers can provide guidance and counseling services using the self-counseling method to create and increase good learning motivation.